The Fire Keeper : a Storm Runner novel - Cervantes, J. C. (Jennifer C.) (2019)
Zane Obispo faces an impossible choice--to save other godborns like himself from the angry gods, or rescue his father, Hurakan, from his eternal prison.
Sequel to: The Storm Runner.
Ages: 8-12
Keywords: Maya mythology -- Fiction; People with disabilities -- Fiction; Fathers and sons -- Fiction; Maya gods -- Fiction